Credit-to-GDP gap: Local versus foreign currency credit - Gjergj Legisi (Graduate Institute of International and Development Studies, 2020)
The credit-to-GDP gap is a fundamental indicator used to identify credit bubbles. Currently, the indicator takes into account aggregate credit as a ratio of GDP, without distinguishing between local and foreign currency. In the Albanian financial system, foreign currency loans comprise about fifty percent of the total credit. Due to the large share of foreign currency loans, this paper evaluates the credit-to-GDP gap by local (Albanian lek) and foreign (Euro and US dollar) currency to assess their performance in identifying credit bubbles. This study concludes that using a modified version of credit-to-GDP gap, which extracts foreign currency fluctuations, provides a better overall performance than the standard approach. In addition, a split credit-to-GDP gap according to local and foreign currency provides similar performance to the standard and modified approach, but offers a more structure-based approach.
Keywords: E44; G01; G18; 330; credit-to-GDP gap; foreign currency credit; countercyclical capital buffer